The Impact of Food Quality and Service Quality on Customer Loyalty: The Mediating Role of Customer Satisfaction - Rahmayoga, Rifanda Rizki; Wiwoho, Gunarso (Journal of Educational Management Research, 2025)
This study aims to analyze the influence of food quality and service quality on customer loyalty, both directly and indirectly through Customer satisfaction as a mediating variable. The research was conducted on customers of Tuman Coffee and Space in Kebumen who had visited the café at least twice a month. A quantitative research method with a descriptive approach and path analysis was employed. Data were collected using questionnaires distributed to 207 respondents. The results show that both food quality and service quality have a significant effect on Customer satisfaction. Furthermore, food quality and service quality also significantly influence customer loyalty. Customer satisfaction is proven to be a significant mediating variable in the relationship between food quality, service quality, and customer loyalty. These findings indicate that improving food and service quality directly impacts Customer satisfaction and loyalty, which in turn supports the business sustainability of Tuman Coffee and Space.